1996
DOI: 10.1073/pnas.93.24.13925
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective isolation of human DNAs from rodent–human hybrid cells as circular yeast artificial chromosomes by transformation-associated recombination cloning

Abstract: Transformation-associated recombination (TAR) can be exploited in yeast to clone human DNAs. TAR cloning was previously accomplished using one or two telomere-containing vectors with a common human repeat(s) that could recombine with human DNA during transformation to generate yeast artificial chromosomes (YACs). On basis of the proposal that broken DNA ends are more recombinogenic than internal sequences, we have investigated if

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 24 publications
(27 reference statements)
2
67
0
Order By: Relevance
“…Southern blot hybridization with a probe of labeled total human DNA showed that the circular YACs derived from YAC77 ranged from ∼50 to 700 kb. This is similar to the size range of YACs (60 to 700 kb) that were recovered previously with the pNKBAC39 vector during TAR cloning of human DNA from hybrid cell lines containing whole human chromosomes (9,24). Similar results were obtained by linearizing the YACs by NotI digestion with an additional set of clones.…”
Section: Overlapping Circular Bacs From a Megabase Size Linear Yac Gesupporting
confidence: 72%
See 1 more Smart Citation
“…Southern blot hybridization with a probe of labeled total human DNA showed that the circular YACs derived from YAC77 ranged from ∼50 to 700 kb. This is similar to the size range of YACs (60 to 700 kb) that were recovered previously with the pNKBAC39 vector during TAR cloning of human DNA from hybrid cell lines containing whole human chromosomes (9,24). Similar results were obtained by linearizing the YACs by NotI digestion with an additional set of clones.…”
Section: Overlapping Circular Bacs From a Megabase Size Linear Yac Gesupporting
confidence: 72%
“…Frequency of loss of this chromosome was no higher than once per 1000 cell divisions. Circular YACs with human and mouse DNA inserts were created either by in vivo ligation (26) or recombination in yeast (9,24,27). While there are no systematic studies, it is clear from published data that circular molecules up to ∼1.0 Mb can be constructed in yeast, and the mitotic stability of these circles is no different from linear YACs of the same size.…”
Section: Discussionmentioning
confidence: 99%
“…Similar requirement for homology is seen in gene targeting in T. brucei (Blundell et al 1996). Recombination during TAR cloning, however, is relatively insensitive to mismatches, as demonstrated by using Alu repeats, which are shorter (∼300 bp) than the target used here (560 bp) and more divergent (85% identity on average) (Larionov et al 1996b;Noskov et al 2003b). The distribution of the non-BES3 clones is similar to that of random telomere targeting in yeast, in which there are imperfect repeats (Louis and Borts 1995).…”
Section: Cloning Bias Of T Brucei Bessmentioning
confidence: 97%
“…The highly transformable Saccharomyces cerevisiae strain VL6-48 (MATa, his3-⌬200, trp1-⌬1, ura3-52, lys2, ade2-101, met14) (8), which has HIS3 deleted was used for transformations. Spheroplasts that enable efficient transformation were generated by using a previously described protocol (1).…”
Section: Methodsmentioning
confidence: 99%
“…Spheroplasts that enable efficient transformation were generated by using a previously described protocol (1). Agarose plugs (100 l) containing approximately 5 g of high molecular weight human DNA were prepared from normal human fibroblasts MRC-5 (American Type Culture Collection) and used for yeast transformation (1,8). Linearized TAR cloning vector (1 g) was added to the DNA-containing plugs before treating with agarase and presented to spheroplasts.…”
Section: Methodsmentioning
confidence: 99%